Comparative Studies on Experimental Procedures for Labeling of Tc-99m with L-Aspartic Acid - Park, Yeong-Jae; Kang, Sung-A; Yeon, Jei-Won; Kim, Ki-Jin (Asian Journal of Chemistry, 2014)
For the labeling of Tc-99m radioisotope with L-aspartic acid (ASP), six different procedures were designed. The key points to the procedures are focused on the phase (solid or solution) used of major reactants (L-aspartic acid sodium salt monohydrate and SnCl2) and the pH of reacting solution. Labeling experiments were carried out according to the procedures at conditions; the concentration ratio ([ASP]/[SnCl2]) = 35-45, temperature = 80 ºC, radioactivity of 99mTc = 5 mCi, reaction time = 1 h. The labeling was investigated by radio-ITLC using methylethyl keton (MEK) and 0.9 % saline solution as solvents, respectively. The labeling yields were determined from the radioactivity distributions in the two solvents. Solid typed SnCl2 gave better yields than solution typed SnCl2. While, regardless of whether L-aspartic acid sodium salt monohydrate was used as solid or solution, there was found a negligible effect on 99mTc labeling. The pH dependence on the 99mTc labeling with L-aspartic acid sodium salt monohydrate was found. The labeling yields were found higher in the following order; weakly acidic and neutral (pH 5-7) > alkaline (pH 10) > acidic (pH 4) media. The best yield (ca. 90 %) was obtained from the procedure that both L-aspartic acid sodium salt monohydrate and SnCl2 were used as solid without adjustment of pH, providing a good method for the preparation of pharmaceutical kits using L-aspartic acid sodium salt monohydrate.